Prenatal Yoga Menurunkan Keluhan Nyeri Punggung Bawah pada Ibu Hamil - Rustiningsih, Titin; Asih, Fransisca Retno; Solihin, Solihin (Jurnal Kebidanan Malakbi, 2022)
Globally, the prevalence of low back pain in pregnancy varies between 34-86%. Prenatal yoga increases flexibility, strength, and endurance of muscles such as the back, abdominal, and pelvic floor muscles. This study aims to determine the effect of prenatal yoga on reducing low back pain in pregnant women. This research method is quasi-experimental with a pre-test and post-test approach with a control group design. A total of 46 pregnant women (23 subjects in each group) who came consecutively and had passed the selection based on inclusion criteria (pregnant women aged 16-31 weeks, experiencing mild to moderate low back pain, willing to be research respondents) and exclusion (pregnant women) with complications, nausea vomiting pregnancy, spinal disorders, multiple pregnancies, taking pain medication, having medical restrictions on physical activity or exercise, and participating in other back pain therapies) were selected as study subjects. Research subjects in the intervention group received prenatal yoga once a week (60 minutes) for eight weeks with the same sequence, while the control group was given education and motivation for pregnancy exercise according to ANC standards using leaflets. Pain measurement using VAS performed before and after the intervention. Data were analyzed using the Mann-Whitney test and paired t-test. The results of the study showed that there was a decrease in low back pain in the prenatal yoga group and the control group (p<0.001). The average decrease in low back pain in the prenatal yoga group was higher (3.57mm) than in the control group (1.76mm). The study concludes that prenatal yoga is a complementary and alternative therapy that is safe and can prevent and reduce complaints of low back pain in pregnant women.